Experimental study on the natural frequency of tunable piezoelectric cantilever plate. (September 2019) - Chen, Lihua; Chang, Liqi; Xue, Jiangtao; Yang, Fenghong
Abstract: PEH (piezoelectric energy harvester) outputs a higher voltage when the natural frequency matches ambient vibration frequency. How to widen working frequency band is a hot issue in study of PEH. In this paper, an auto-tuning PEH is presented by attaching a box to each corner of its free sides and a ball is placed in each box. Change of the balls position makes natural frequency of PEH variable, which expands working bandwidth of the device to accommodate complex ambient vibration. Fixing the equipment on experimental platform by designing fixture, hammering experiments are carried out to measure natural frequency of the structure when balls are in different positions. It is found that the maximum and minimum natural frequencies exist in the auto-tuning PEH, which form a resonance bandwidth. Moreover, there are multiple position combinations of two balls at the same natural frequency in the range of resonance bandwidth. Fixed the apparatus on exciter by the fixture, and a constant excitation frequency is selected in the bandwidth to perform auto-tuning experiments on the instrument. It is observed that location of balls is automatically changed to make natural frequency of the system coincide with the excitation, and the law of variation in balls position is obtained. The converter is subjected to sweeping experiments through an exciter and an oscilloscope. Using voltage-frequency diagrams, it is shown that the auto-tuning PEH outputs a higher voltage and its frequency band is wider when the ball rolls freely compared to two cases where balls are fixed.